Persepsi Pasien Umum terhadap Biaya Perawatan di RS Hikmah Citra Medika Sengkang - A Nur Azizah; Idarwati Mustafa; Eka Wulansari; Iswi Ramadhani B (Lentera Pena Cendekia, 2025)
Patient perception of healthcare costs in hospitals is a key factor influencing patient satisfaction. Hospitals that can provide clear cost information and quality medical services are more likely to gain patients' trust, which in turn contributes to higher patient satisfaction with the costs they incur. This study aims to explore the general patient perception of healthcare costs at RS Hikmah Citra Medika Sengkang. The study used a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with 10 inpatients during March-April 2025. Participants were selected through purposive sampling, and data analysis was conducted using the Colaizzi method. The results show that cost transparency, the quality of healthcare services, and comfort during treatment are the main factors influencing patient perceptions of the costs they pay. Patients feel more comfortable when they receive transparent cost information before treatment, which allows them to financially prepare. Additionally, the quality of medical services provided by healthcare professionals and hospital facilities also plays a significant role in shaping positive perceptions of costs. The safety and comfort during treatment, related to the hospital's facilities and atmosphere, also affect patient satisfaction with the costs incurred. This study concludes that cost transparency and high-quality service are crucial for building patient trust and improving satisfaction with the incurred healthcare costs. Hospitals need to continue enhancing information transparency and service quality to maintain positive patient perceptions of healthcare costs.